Knowledge, attitude and practice of self medication among undergraduate medical students in a teaching institution - Sundararajan, Anbarasi; Thangappan, Ashok Kumar (International Journal of Basic & Clinical Pharmacology, 2018)
Background: Self medication is the usage of medicines without the advice of the physicians, without proper diagnosis of the illnesses and without any prescription. Medical students are more liable to self medicate themselves due to their partial knowledge and easy availability of drugs. This study was conducted to assess the pattern of self medication in undergraduate medical students. This study was conducted to assess the knowledge, attitude and practice of self medication among undergraduate medical students in Kanyakumari government medical college, a teaching institute in South Tamilnadu. Methods: A self-designed questionnaire was given to the undergraduate medical students who were willing to participate in the study. 264 students participated of which 111 were males and 153 were females in the age group of 17-24 yrs. Data were collected. Results were given as percentages and counts. Results: The prevalence of self medication was found to be 85.2% which is very high. Commonest reason was its usefulness in mild illnesses (89.3%). The commonly used group of drugs was antipyretics (98.6%), ointments (44.4%) and antibiotics (41.3%). The commonest source of information was old prescriptions (62.8%). The common ailments were fever (88%) and cough and cold (80.4%). Ironically 72.88% opined that self medication should not be practiced. Conclusions: Increased prevalence of self medication among medical students implies that they are highly exposed to the adverse effects of drugs. Steps should be taken to curtail self medication among medical students by educating and creating awareness among them.